(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses effective strategies for teaching English to young learners. It highlights the importance of play-based learning, songs, storytelling, interaction, and movement to enhance language acquisition. The study emphasizes the role of a positive learning environment, parental involvement, and structured routines in fostering English language development among children.